Prevention of Cardiomyopathy in Transfusion-Dependent Homozygous Thalassaemia Today and the Role of Cardiac Magnetic Resonance Imaging - Athanassios Aessopos; Vasilios Berdoukas; Maria Tsironi (Advances in Hematology)
Transfusion and iron chelation therapy revolutionised survival and reduced morbidity in patients with transfusion-dependent beta thalassaemia major. Despite these improvements, cardiac disease remained the most common cause of death in those patients. Recently the ability to determine the degree of cardiac iron overload, through cardiac magnetic resonance imaging (CMR) has allowed more logical approaches to iron removal, particularly from the heart. The availability of two oral chelators, deferiprone and deferasirox has reduced the need for the injectable chelator deferrioxamine and an additional benefit has been that deferiprone has been shown to be more cardioprotective than deferrioxamine. This review on the prevention of cardiac disease makes recommendations on the chelation regime that would be desirable for patients according to their cardiac iron status as determined by CMR determined by CMR. It also discusses approaches to chelation management should CMR not be available.